Do teaching experience, continuing professional development, and teaching styles matter in teaching quality in higher education? perception of Libyan students at the University of Zawia - Elhatab, Abdesalam; Muhammad, Haslinah; Mustafa, Hasri; Osman, Mohammad Noor Hisham (Human Resource Management Academic Research Society, 2024)
Despite an increasing number of Libyan lecturers sent abroad on government grants to enhance their education and contribute to the economic and social advancement of Libyan society, higher education in Libya faces numerous challenges, notably the low ranking of its universities. Libya's exclusion from global quality indices stems from various factors, including inadequate teaching quality, a prevalence of traditional teaching methodologies, and a misalignment between higher education outputs and the demands of the labor market.This study aims to explore the specific factors influencing the quality of accounting education from the perspective of students, focusing on teaching experience, continuing professional development, and teaching methodologies. A face-to-face questionnaire was administered to 281 accounting students purposively selected from 31 undergraduate classes at the University of Zawia in Libya. Descriptive and inferential statistics were analyzed using SPSS and SEM-PLS. The findings indicate a significant impact of these factors on teaching quality. However, contrary to student expectations, student-centered teaching styles were found to have an insignificant effect on teaching quality. This discrepancy suggests that while teacher centered approaches may be perceived as effective by students, they fail to equip students with the necessary skills demanded by the labor market, which student-centered approaches address. Hence, there is a pressing need for policymakers to prioritize the enhancement of higher education quality, particularly in the realm of accounting education. This necessitates multifaceted interventions, including providing resources for faculty development, investing in continuing professional development initiatives, and facilitating the transition from teacher-centered to student-centered teaching approaches through training programs and workshops.